Arabidopsis thaliana—Aphid Interaction - Louis, Joe (American Society of Plant Biologists, 2012)
Aphids are important pests of plants that use their stylets to tap into the sieve elements to consume phloem sap. Besides the removal of photosynthates, aphid infestation also alters source-sink patterns. Most aphids also vector viral diseases. In this chapter, we will summarize on recent significant findings in plant-aphid interaction, and how studies involving Arabidopsis thaliana and Myzus persicae (Sülzer), more commonly known as the green peach aphid (GPA), are beginning to provide important insights into the molecular basis of plant defense and susceptibility to aphids. The recent demonstration that expression of dsRNA in Arabidopsis can be used to silence expression of genes in GPA has further expanded the utility of Arabidopsis for evaluating the contribution of the aphid genome-encoded proteins to this interaction.